Nanosecond Laser–Fabricated Monolayer of Gold Nanoparticles on ITO for Bioelectrocatalysis - Hitaishi, Vivek Pratap; Mazurenko, Ievgen; Vengasseril Murali, Anjali; de Poulpiquet, Anne; Coustillier, Gaëlle; Delaporte, Philippe; Lojou, Elisabeth (Frontiers in Chemistry, 2020)
Redox enzymes can be envisioned as biocatalysts in various electrocatalytic-based devices. Among factors that play roles in bioelectrochemistry limitations, the effect of enzyme-enzyme neighboring interaction on electrocatalysis has rarely been investigated, although critical in vivo. We report in this work an in-depth study of gold nanoparticles prepared by laser ablation in the ultimate goal of determining the relationship between activity and enzyme density on electrodes. Nanosecond laser interaction with nanometric gold films deposited on indium tin oxide support was used to generate in-situ gold nanoparticles (AuNPs) free from any stabilizers. A comprehensive analysis of AuNP size and coverage, as well as total geometric surface versus electroactive surface is provided as a function of the thickness of the treated gold layer. Using microscopy and electrochemistry, the long-term stability of AuNP-based electrodes in the atmosphere and in the electrolyte is demonstrated. AuNPs formed by laser treatment are then modified by thiol chemistry and their electrochemical behavior is tested with a redox probe. Finally, enzyme adsorption and bioelectrocatalysis are evaluated in the case of two enzymes, i.e. the Myrothecium verrucaria bilirubin oxidase and the Thermus thermophilus laccase. Behaving differently on charged surfaces, they allow demonstrating the validity of laser treated AuNPs for bioelectrocatalysis.